Resistance-Trained Individuals Can Underestimate the Intensity of the Resistance Training Session: An Analysis Among Sexes, Training Experience, and Exercises - Santos, Wellington Martins dos; Tavares Junior, Antonio Carlos [UNESP]; Braz, Tiago Volpi; Lopes, Charles Ricardo; Brigatto, Felipe Alves; Santos, Júlio Wilson dos [UNESP] (Wolters Kluwer, 2022)
Dos Santos, WM, Tavares Junior, AC, Braz, TV, Lopes, CR, Brigatto, FA, and Dos Santos, JW. Resistance-trained individuals can underestimate the intensity of the resistance training session: An analysis among genders, training experience, and exercises. J Strength Cond Res 36(6): 1506-1510, 2022 - Resistance training (RT) promotes improvements in healthy parameters for young to elderly adults and athletes' performance. Strength and muscle mass improvements are dependent on exercise intensity. This study verifies whether 53 healthy young adults underestimate exercise intensity in 3 different exercises, such as bench press (BP), biceps curl (BC), and leg press 45° (LP). Researchers asked the subjects How much load do you use to perform 10 repetitions in this exercise usually in workout routines? in each exercise. Individuals warmed up and then performed as many repetitions as possible until they reached the concentric failure. Deviations from data normality were found by using Levene's test; the number of repetitions per exercise within sex was tested by using Friedman's test and Conover's post hoc and Kruskal-Wallis tests to compare the number of repetitions between sex and RT experience. We correlated the number of repetitions and training experience using the Spearman test. The number of repetitions for both groups (male and female) is greater than 8-12 repetitions for BC and LP and BP of the female group, except for men who perform around 8-12 repetitions on BP. Frequency of maximal repetitions reached for 8-12 repetitions for women was 12% for BP, 28% for BC, and 28% for LP. The frequency men reached was 46.5% for BP, 14.3% for BC, and 14.3% for LP. Training experience did not influence the number of repetitions reached. Resistance training practitioners underestimate exercise load (56% of total sample) to be independent of experience. Women underestimate exercise load more than men. Based on the present results, it is possible to state that RT should not be prescribed considering a predefined number of repetitions and a linked percentage of loads, without the guidance for frequent adjustments of loads, according to the exercise performed.
Keywords: load; repetitions; strength exercises